SIKAP RUMAH TANGGA TERHADAP KOMODITAS CABAI KERING (APLIKASI PENDEKATAN THEORY OF PLANNED BEHAVIOR) - Fachruddin, Achmad; Firdaus, Muhammad; Tinaprilla, Netti (Forum Agribisnis, 2014)
Dried chillies arepotential to substitute fresh chillies when the price of fresh chillies significantly increases, and its purchases were expected to determine by the household consumerâs attitude. The aims of this researchare 1) to examine the household attitudes on dried chilies purchasing bythe Theory of Planned Behavior approach, 2) to determine the determinant factors ofdried chilli buying intention, and 3) to estimate the cross-elasticity of dried chili againsts fresh chilli. The results showed that household consumer attitude towards the purchase of dried chillies, in term of subjective norms,perceived behavioral control, and purchase intention, Â are in medium category. The determinant factors on purchase intention of dried chilies (Î± = 10 percent) are the subjective norms, attitudes towards the purchase of dried chilies, and household income per month. The dried chilli cross-elasticity valueis very inelastic (0.069). Due to that, the policy implications in encouraging the dried chilli purchasing are the socialization of the dried chilliâs benefits and sustain the avaibility of dried chillies in traditional markets.